WORK-LIFE BALANCE POLICIES AND THEIR EFFECT ON EMPLOYEE JOB SATISFACTION IN REMOTE WORK SETTINGS - Hans Cristian; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The rapid proliferation of remote work has fundamentally altered the work-life interface, making organizational Work-Life Balance (WLB) policies more critical than ever for employee job satisfaction. This critical review synthesizes existing literature to evaluate the efficacy of these policies in remote settings, revealing significant theoretical and methodological shortcomings. The analysis demonstrates that dominant frameworks often promote a flawed "one-size-fits-all" approach, overlooking how individual circumstances and unexamined power dynamics can cause standardized policies to inadvertently perpetuate inequality. Furthermore, reliance on cross-sectional data and simplistic measures of job satisfaction limits causal understanding. The review concludes that the mere provision of policies is insufficient; their success is contingent upon a supportive organizational culture and faithful implementation. It argues for a necessary paradigm shift from standardized benefits towards personalized, co-created work arrangements, and calls for future research to adopt longitudinal and qualitative methods to better capture the complex relationship between policy, power, and sustained employee well-being in the remote work era.